(untitled) (Global Journal of Science Frontier Research, 2020)
Mathematical models considering a dense crowd as a soft solid predicted counterclockwise collective movement during rock concerts. This article explains that if mathematical modeling of dense crowds as soft solids works for predicting the collective behavior of crowds at rock concerts, it is because everything material (from the smallest elementary particle to humans and even stars) is a material body and torus-shaped nonlinear electromagnetic field (NEMF). We can come to the same conclusion for the crowd behavior at rock concerts, knowing that at positive emotions our NEMFs spin clockwise, according to Russian measurements. Nonlinear physics teaches that vortices spin clockwise and suck energy. When the energy sucked by the NEMFs of the crowd reaches the critically high value, it triggers collective movement of the crowd counterclockwise to release some of the extra energy. Nonlinear physics teaches that anti-vortices spin counterclockwise and emit energy upward, which means that some of the extra excitation energy will be released in the atmosphere.